Trunk, Mass Grasp, Knee, and Hip Muscle Performance in CrossFit Participants: Reference Values According to Participants' Sex and Limb Dominance - Ana Luiza R Rodrigues; Renan A. Resende; Livia S. Pogetti; Thiago R. T. Santos; Henrique M. P. Faria; Mauro H. Chagas; Juliana M Ocarino (International Journal of Sports Physical Therapy, 2023)
# Background